2019
DOI: 10.1088/1361-648x/ab21ec
|View full text |Cite
|
Sign up to set email alerts
|

Small non-uniform basal crystal fields in HVPE free-standing GaN:Mg as evidenced by angular dependent and frequency-dependent EPR

Abstract: We studied thin-film and free-standing Mg-doped GaN using multi-frequency electron paramagnetic resonance (EPR) at 3–3.5 K and 9.4–130 GHz. Free-standing samples exhibit a highly anisotropic intensity, varying by a factor of 20 from 0° to 60°. In contrast, the intensity of the thin-film samples is significantly more isotropic, varying by no more than 10% over the same range of angles. The angular dependent intensity can be modeled in both free-standing and thin-film samples similarly to the g-factor anisotropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…2 The possibility to access electron spin dynamics at much higher, i.e., Terahertz (THz) frequencies is attractive. Large energies permit better understanding of spin dynamics in single-molecule magnets, for example, 3,4 and allow investigation of systems with large zero-field splitting such as in transition metal complexes, 5,6 or in ultrawide-bandgap semiconductors, e.g., SiC [7][8][9] and group-III nitrides 10,11 for quantum technologies, or the recently emerging monoclinic gallium oxide for high voltage electronic applications. [12][13][14][15][16][17][18][19] To bring spin resonances into the THz range, superconducting magnets reaching large magnetic fields are necessary.…”
mentioning
confidence: 99%
“…2 The possibility to access electron spin dynamics at much higher, i.e., Terahertz (THz) frequencies is attractive. Large energies permit better understanding of spin dynamics in single-molecule magnets, for example, 3,4 and allow investigation of systems with large zero-field splitting such as in transition metal complexes, 5,6 or in ultrawide-bandgap semiconductors, e.g., SiC [7][8][9] and group-III nitrides 10,11 for quantum technologies, or the recently emerging monoclinic gallium oxide for high voltage electronic applications. [12][13][14][15][16][17][18][19] To bring spin resonances into the THz range, superconducting magnets reaching large magnetic fields are necessary.…”
mentioning
confidence: 99%
“…With deep levels transient spectroscopy (DLTS), Kanegae et.al [ 9 ] observed that E 3 ( E c −0.60 eV) and H 1 ( E v +0.87 eV) are dominating traps in n-type GaN, and they attributed H 1 trap to the gallium vacancy or C related defects. Sunay et.al [ 10 ] applied electron paramagnetic resonance (EPR) to find that the hole is around the Mg acceptor. In addition, by using positron annihilation spectroscopy (PAS), EPR, and density functional theory (DFT), Bardeleben et.al [ 11 ] found that the isolated N interstitial is unstable and prefers to form a split interstitial configuration, which is located at E c −1.0 eV.…”
Section: Introductionmentioning
confidence: 99%
“…2 The possibility to access electron spin dynamics at much higher, i.e., Terahertz (THz) frequencies is attractive. Large energies permit better understanding of spin dynamics in single-molecule magnets, for example, 3,4 and allow investigation of systems with large zero-field splitting such as in transition metal complexes, 5,6 or in ultrawide-bandgap semiconductors, e.g., SiC 7-9 and group-III nitrides 10,11 for quantum technologies, or the recently emerging monoclinic gallium oxide for high voltage electronic applications. [12][13][14][15][16][17][18][19] To bring spin resonances into the THz range, superconducting magnets reaching large magnetic fields are necessary.…”
mentioning
confidence: 99%